2019
DOI: 10.3390/ijms20061479
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Cotton (Gossypium hirsutum) Genes That Are Differentially Expressed in Cadmium Stress Tolerance

Abstract: High concentrations of heavy metals in the soil should be removed for environmental safety. Cadmium (Cd) is a heavy metal that pollutes the soil when its concentration exceeds 3.4 mg/kg. Although the potential use of cotton to remediate heavy Cd-polluted soils is known, little is understood about the molecular mechanisms of Cd tolerance. In this study, transcriptome analysis was used to identify Cd tolerance genes and their potential mechanisms in cotton. We exposed cotton plants to excess Cd and identified 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Some reports showed that the quantity of DEGs under salt stress varied from 3800 to 22,000 in cotton [ 51 , 52 ]. Han et al identified 4627 DEGs in cotton under cadmium (Cd) toxicity [ 53 ]. In the present study, around 2000 and 2500 DEGs ( p -value < 0.05, and |log 2 (Fold Change) | ≥ 1.)…”
Section: Discussionmentioning
confidence: 99%
“…Some reports showed that the quantity of DEGs under salt stress varied from 3800 to 22,000 in cotton [ 51 , 52 ]. Han et al identified 4627 DEGs in cotton under cadmium (Cd) toxicity [ 53 ]. In the present study, around 2000 and 2500 DEGs ( p -value < 0.05, and |log 2 (Fold Change) | ≥ 1.)…”
Section: Discussionmentioning
confidence: 99%
“…For example, on the one hand, gene expression in ROS way and ion balance maintenance, such as Ca 2+ signaling pathway and MAPK, MYB transcription factor [62,63,64], programmed cell death [65,66,67]. And then the GSH, as the main way to remove ROS under the condition of high concentration, can not only response to heavy metal ions [68], also can response to salt stress ion [69]. At last, the balance of ions, such as anthocyanins were associated with the salt stress [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Then the GUS gene was replaced with two target gene LOC-1 and LOC-2 , which were added CaMV35s promoter and Nos terminator at 5’ and 3’ end, respectively. The constructed plasmid was transformed into Arabidopsis thaliana to verify its functions [ 31 ].…”
Section: Methodsmentioning
confidence: 99%